The absorption-dominated model for the X-ray spectra of type I active galaxies: MCG-6-30-15 - Miller, L; Turner, T; Reeves, J (2009)
MCG-6-30-15 is the archetypal example of a type I active galaxy showing broad "red-wing" emission in its X-ray spectrum at energies below the 6.4 keV Fe K-alpha emission line and a continuum excess above 20 keV. Miller et al. (2008) showed that these spectral features could be caused by clumpy absorbing material, but Reynolds et al. (2009) have argued that the observed Fe K-alpha line luminosity is inconsistent with this explanation unless the global covering factor of the absorber(s) is very low. However, the Reynolds et al. calculation effectively considers the only source of opacity to be the Fe K bound-free transition and neglects the opacity at the line energy: correction to realistic opacity decreases the predicted line flux by a large factor. We also discuss the interpretation of the covering factor and the possible effect of occultation by the accretion disk. Finally, we consider a model for MCG-6-30-15 dominated by clumpy absorption, which is consistent with global covering factor 0.45, although models that include the effects of Compton scattering are required to reach a full understanding. Variations in covering fraction may dominate the observed X-ray spectral variability.